Déjà-vu? Neural and behavioural effects of the 5-HT4 receptor agonist, prucalopride, in a hippocampal-dependent memory task - de Cates, AN; Wright, LC; Martens, MAG; Gibson, D; Türkmen, C; Filippini, N; Cowen, PJ; Harmer, CJ; Murphy, SE (Springer Nature, 2021)
Cognitive deficits commonly accompany psychiatric disorders but are often underrecognised, and difficult to treat. The 5-HT4 receptor is a promising potential treatment target for cognitive impairment because in animal studies 5-HT4 receptor agonists enhance hippocampal-dependent memory processes. To date, there has been little work translating these effects to humans. We tested whether short-term administration of the 5-HT4 partial agonist, prucalopride, modified behavioural and neural (fMRI) memory processing in 44 healthy human volunteers using an experimental medicine model. We found that participants who had received six days of prucalopride treatment were significantly better at recalling previously seen neutral images and distinguishing them from new images. At a neural level, prucalopride bilaterally increased hippocampal activity and activity in the right angular gyrus compared with placebo. Taken together, these findings demonstrate the potential of 5-HT4-receptor activation for cognitive enhancement in humans, and support the potential of this receptor as a treatment target for cognitive impairment.